Serum hepcidin levels and muscle iron proteins in humans injected with low‐ or high‐dose erythropoietin. (3rd May 2013) - Robach, Paul; Recalcati, Stefania; Girelli, Domenico; Campostrini, Natascia; Kempf, Tibor; Wollert, Kai C.; Corbella, Michela; Santambrogio, Paolo; Perbellini, Luigi; Brasse‐Lagnel, Carole; Christensen, Britt; Moutereau, Stéphane; et al.
Abstract Inhibition of hepcidin expression by erythropoietic signals is of great physiological importance; however, the inhibitory pathways remain poorly understood. To investigate (i) the direct effect of erythropoietin (Epo) and (ii) the contribution of putative mediators on hepcidin repression, healthy volunteers were injected with a single dose of Epo, either low (63 IU/kg, n = 8) or high (400 IU/kg, n = 6). Low‐dose Epo provoked hepcidin down‐modulation within 24 h; the effect was not immediate as hepcidin circadian variations were still present following injection. High‐dose Epo induced no additional effect on the hepcidin response, that is hepcidin diurnal fluctuations were not abolished in spite of extremely high Epo levels. We did not find significant changes in putative mediators of hepcidin repression, such as transferrin saturation, soluble transferrin receptor, or growth differentiation factor 15. Furthermore, the potential hepcidin inhibitor, soluble hemojuvelin, was found unaltered by Epo stimulation. This finding was consistent with the absence of signs of iron deficiency observed at the level of skeletal muscle tissue. Our data suggest that hepcidin repression by erythropoietic signals in humans may not be controlled directly by Epo, but mediated by a still undefined factor.